Determinants of Use of the Indonesian Standard Quick Response Code (QRIS) on MSMEs in Ternate City - Rheza Pratama; Hartaty Hadady; Muhsin N. Bailusy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims tooanalyze the effect of perceived risk and ease of use8on the decision to transact using QRIS on MSME actors in Ternate City, either partially or simultaneously. This research0is a hypothesis testing research (Hypothesi9testing) which aims to test the hypothesis proposed by the Research Team. The analytical model used in this study is a multiple linear regression equation model to analyze the effect of risk perception and user convenience6on the decision to make payments with2QRIS. Collecting data using a questionnaire with a purposive sampling technique as many as 60 respondents. Risk Perception and User Convenience contributed 72.2% to the decision to transact using QRIS in Ternate City MSME actors, the remaining 27.8% was explained by other variables outside the research model. The results of the t-test concluded that Risk Perception had no significant effect on the decision to transact using QRIS on MSME actors in Ternate City, while User Ease had a positive and significant effect on the decision to transact using QRIS on MSME actors in Ternate City. Based on the Anova Test,f-count value of 52.133 > t-table (2.766), it can be concluded that the variables of Risk Perception and Ease of Use together can influence the decision to transact using QRIS.